Job Stress among Night-Shift Nurses in Critical Care Units (Medical Forum Monthly, 2025)
Objective: To assess job stress among night-shift critical care nurses under the working hour’s system in effect.Study Design: Quantitative cross-sectional studyPlace and Duration of Study: This study was conducted at the College of Nursing, Adult Nursing, University of Babylon from 12th September 2024 to 29th October 2024.Methods: 178 night-shift critical care nurses working in three randomly selected governmental hospitals were enrolled. Nurses were selected by the availability sampling method. Data were collected by demographic characteristics and The Expanded Nurses Stress Scale (ENSS).Results: Females those working overtime in the private sector were significantly more likely to experience high stress.Conclusion: Most of the females have high level of job stress and there are significant relationships between job stress and gender, level of income, level of education, years of experience, and type of unit.